KARAKTERISASI HIKIKOMORI PADA TOKOH SAGIRI DALAM ANIME EROMANGA SENSEI - Atikah Hanum Yuliwarto (Japanology: The Journal of Japanese Studies, 2022)
The hikikomori phenomenon was first introduced by psychiatrist Saito Tamaki in his book entitled Shakaiteki Hikikomori: Owaranai Shishunki in 1998. This research aimed to analyze the characterization of a hikikomori in character Izumi Sagiri using the semiotic theory of Charles Sanders Peirce. The object of this research is anime Eromanga Sensei by Tsukasa Fushimi and produced by A-1 Picture in 2017. This study is a descriptive qualitative study using data in the form of verbal and visual dialogue in the anime that will be selected and analyzed based on existing signs in accordance with Charles Sanders Peirce's semiotic theory. The results of this study indicate that the character Sagiri has several signs of characterizations of a hikikomori that are compatible with the real world.